2021
DOI: 10.1177/02692163211004403
|View full text |Cite
|
Sign up to set email alerts
|

Culture in the spotlight—cultural adaptation and content validity of the integrated palliative care outcome scale for dementia: A cognitive interview study

Abstract: Background: Dementia is a life-limiting disease with high symptom burden. The Integrated Palliative Care Outcome Scale for Dementia (IPOS-Dem) is the first comprehensive person-centered measure to identify and measure palliative care needs of people with dementia. However, such a measure is missing in the German health care system. Aim: To develop a culturally adapted German version of the IPOS-Dem and determine its content validity as a foundation for comprehensive psychometric testing. Design: Cognitive inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
(58 reference statements)
1
6
1
Order By: Relevance
“…However, previous studies noted that some logical or structural problems could not be covered by the four-stage model. 27–29 We did not identify the same findings in the current study. It might be due to the fact that the related problems were already addressed in the expert review.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…However, previous studies noted that some logical or structural problems could not be covered by the four-stage model. 27–29 We did not identify the same findings in the current study. It might be due to the fact that the related problems were already addressed in the expert review.…”
Section: Discussioncontrasting
confidence: 68%
“…These results match those observed in previous studies. 26 , 27 In many instances, participants were not aware of their misunderstandings, which were only identified through verbalization of their thought processes or by probing. The cognitive interviewing methodology could understand how targeted subjects comprehend and generate their answers to the question, aiming to reveal problems concerning comprehension, information retrieval, judgment, and response process.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the results confirmed the need to adapt the formal translation of palliative care phases to the cultural context of the German specialist palliative care setting and consider setting specific wording/language as well as educational needs of professionals. The necessity of cultural adaptations was also reported by other studies that translated patient reported outcomes [ 28 , 31 34 ].…”
Section: Discussionsupporting
confidence: 54%
“…Care staff score 27 items in the IPOS-Dem with a Likert scale (0 to 4) [ 9 ]. Hodiamont et al [ 10 ] translated the IPOS-Dem from English to German for German health professionals and family members.…”
Section: Introductionmentioning
confidence: 99%